Investigation of Mechanical Properties of FDM-Processed Acacia concinna–Filled Polylactic Acid Filament - S. Muthu Natarajan; S. Senthil; P. Narayanasamy (International Journal of Polymer Science)
In this work, an Acacia concinna filler was blended in a polylactic acid matrix using a single-screw extruder. A composite filament material made from an extruder was used to fabricate polylactic acid/25 wt% A. concinna (PLA/25 wt% AC) composites via a fused deposition modeling (FDM) technique. Composites were fabricated by varying layer thickness, infill density, and printing speed based on Taguchi L9 experimental design. Tensile, flexural, and impact tests were conducted on the printed composite samples as per the ASTM standards. The significance of factors impacting the mechanical properties was determined using analysis of variance. To estimate the strength of PLA/AC composites, mathematical models were developed. In addition, the fractured specimen was examined using scanning electron microscopy to determine the mechanism of fracture. Both the layer height and the infill percentage exhibited a positive influence on strength, which suggests that the layer height or the infill percentage, or both, will increase the material’s strength. The printing speed had a negative influence on the strength, which indicates that the strength decreases as the printing speed increases. The findings suggested that PLA/AC composites could be used to fabricate high-strength, lightweight components using FDM.